MODEL RESOLUSI KONFLIK PENGASUHAN ANAK DALAM KELUARGA MUSLIM PEKERJA GANDA: PERSPEKTIF PSIKOLOGI HUKUM KELUARGA ISLAM BERBAHASIS MAQASHID AL-SYARI'AH - Muhammad Jamaludin Faiz (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The increasing number of Muslim dual-earner families in the modern era has created new dynamics in child-rearing practices that potentially lead to parenting conflicts between spouses. Parenting conflicts may arise from role conflicts, differences in parenting values and styles, economic pressures, time constraints, and ineffective family communication. This study aims to analyze parenting conflicts in Muslim dual-earner families, examine the perspective of Islamic family law psychology on such conflicts, and formulate a parenting conflict resolution model based on maqāṣid al-sharī‘ah. This research employs a qualitative approach using a narrative literature review of relevant primary and secondary sources. The findings indicate that the psychological perspective of Islamic family law provides a comprehensive understanding of parenting conflicts by emphasizing parental rights and obligations, principles of deliberation, justice, and shared responsibility. Integrating maqāṣid al-sharī‘ah as the foundation of conflict resolution offers a normative and ethical framework oriented toward public welfare, particularly the protection of religion, life, intellect, lineage, and property of the child. The proposed maqāṣid-based parenting conflict resolution model contributes to strengthening resilience and harmony in Muslim dual-earner families amid contemporary challenges.